2011
DOI: 10.1073/pnas.1018771108
|View full text |Cite
|
Sign up to set email alerts
|

T-cell triggering thresholds are modulated by the number of antigen within individual T-cell receptor clusters

Abstract: T cells react to extremely small numbers of activating agonist peptides. Spatial organization of T-cell receptors (TCR) and their peptide-major histocompatibility complex (pMHC) ligands into microclusters is correlated with T-cell activation. Here we have designed an experimental strategy that enables control over the number of agonist peptides per TCR cluster, without altering the total number engaged by the cell. Supported membranes, partitioned with grids of barriers to lateral mobility, provide an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
208
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(223 citation statements)
references
References 43 publications
13
208
1
Order By: Relevance
“…Activation violates the attenuation steadystate, and the cell is shifted to a preferred activated state. In addition, we and other investigators showed that Ag density, and not quantity, is the decisive factor in activation of a T cell and that the minimal number of pMHC-I complexes/TCR cluster required for the activation is approximately four (24,57). Our results suggest that, in addition to this minimal activation requirement, maximal cluster activation might exist, as well.…”
Section: Discussionsupporting
confidence: 69%
“…Activation violates the attenuation steadystate, and the cell is shifted to a preferred activated state. In addition, we and other investigators showed that Ag density, and not quantity, is the decisive factor in activation of a T cell and that the minimal number of pMHC-I complexes/TCR cluster required for the activation is approximately four (24,57). Our results suggest that, in addition to this minimal activation requirement, maximal cluster activation might exist, as well.…”
Section: Discussionsupporting
confidence: 69%
“…The triggering chemical thresholds are very high for SLB experiments, 0.2 pMHC per 1 ”m 2 , which corresponds to ∌16 pMHC beneath the cell (28). At least four pMHCs within a single TCR cluster spanning 400 × 400 nm 2 and containing 18-100 TCRs are sufficient to induce the Ca 2+ flux (71). TCR-pMHC clusters form and begin to organize actin machinery, eliciting transport and IS formation with distal, peripheral, and central supramolecular activation clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The recent application of advanced optical techniques (10-13) in combination with substrate patterning and functionalization (14,15) is providing detailed information on how the lateral organization of a variety of molecules located on both sides of the immunological synapse contributes to controlling T-cell activation. Specifically, single-molecule dynamic approaches and superresolution optical nanoscopy experiments have provided indisputable proof that many receptors on the cell membrane organize in small nanoclusters before ligand activation (16).…”
mentioning
confidence: 99%